Strategi Dukungan Keluarga dalam Mendukung Perkembangan sosial Anak dengan Down Syndrome berbasis Ekologi Bronfenbrenner - Mulyani, Sri; Azizah, Nur (Da'wah Faculty of UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
Children with Down Syndrome face complex challenges in physical, cognitive, and social aspects, so they require intensive support from the immediate environment, especially the family. Parental support is a significant factor in shaping children's social skills. This study aims to examine family support strategies in the social development of children with Down Syndrome through the ecological perspective of Bronfenbrenner. The study used a qualitative approach with in-depth interviews and participatory observation of families with children with Down Syndrome. Thematic analysis was conducted to identify forms of family support and the obstacles to providing it. The results of the study show that parental support for children with Down Syndrome includes emotional, social, and educational support. Parents provide affection, involve children in social activities, and accompany the learning and therapy process. However, families face obstacles in the form of limited information, psychological pressure, and limited access to services. To overcome this, adaptive parenting training for parents is recommended, strengthening collaboration between families, schools, and professionals (E.g., Doctors, Psychiatrists, Psychologists, Counselors, Therapists) that create layered support according to Bronfenbrenner's ecological theory, so that children can develop social skills optimally. Anak dengan Down Syndrome menghadapi tantangan kompleks dalam aspek fisik, kognitif, dan sosial sehingga memerlukan dukungan intensif dari lingkungan terdekat, khususnya keluarga. Dukungan orang tua menjadi faktor utama dalam membentuk keterampilan sosial anak. Penelitian ini bertujuan mengkaji strategi dukungan keluarga dalam perkembangan sosial anak dengan Down Syndrome melalui perspektif ekologi Bronfenbrenner. Penelitian menggunakan pendekatan kualitatif dengan wawancara mendalam dan observasi partisipatif terhadap keluarga yang memiliki anak Down Syndrome. Analisis tematik dilakukan untuk mengidentifikasi bentuk dukungan keluarga dan kendala dalam memberikan dukungan keluarga. Hasil penelitian menunjukkan bahwa dukungan orang tua terhadap anak Down Syndrome mencakup dukungan emosional, sosial, dan edukatif. Orang tua memberikan kasih sayang, melibatkan anak dalam aktivitas sosial, serta mendampingi proses belajar dan terapi. Namun, keluarga menghadapi hambatan berupa keterbatasan informasi, tekanan psikologis, dan akses layanan yang terbatas. Untuk mengatasi hal ini, direkomendasikan pelatihan pengasuhan adaptif bagi orang tua, penguatan kolaborasi antara keluarga, sekolah, dan tenaga professional (Dokter, Psikiater, Psikolog, Konselor, Terapis) yang menciptakan dukungan berlapis sesuai teori ekologi Bronfenbrenner, sehingga anak dapat mengembangkan keterampilan sosial secara optimal.